35/#953 Quantity over equity: disparities in the distribution of the U.S. gynecologic oncology workforce. (4th December 2022) - Desravines, Nerlyne; Desjardins, Michael; Curriero, Frank; Fader, Amanda Nickles
Abstract : Objectives: Access-to-care disparities are growing as gynecologic oncologist (GON) demand increases amidst rising gynecologic cancer rates. We characterized the geospatial distribution of the U.S. GON workforce relative to at-risk women over 20 years. Methods: We utilized two U.S. physician registries to identify the 2001–2020 GON workforce. Practice locations were aggregated to county levels. Rural/urban were noted based on census designations. Choropleth maps were used to visually assess the spatial variation of the GON workforce relative to the at-risk female population and correlated with patterns in rurality. Results: Between 2001–2020, the GON workforce increased steadily, plateauing circa 2017 ( figure 1 ). By 2020, there were 1, 178 active GONs; 51.5% were early-to-mid career and 98.3% practiced in urban areas (representing only 37.3% of all counties). A disparity in practice geography was identified, with 1.09 GONs per 100, 000 women in urban areas compared to 0.1 GONs per 100, 000 women in rural areas (p < 0.0001). In total, 2, 867 counties (representing 57.5 million at-risk women) did not have a GON. Additionally, there was no increase in rural GONs observed over time with only 1.7% in 2016 – 2020 relative to 2.2% in 2001–2005. Of the rural providers, fewer were early-to-mid career (23.5%) compared to late-career (76.5%); this trend persisted throughout all periods ( figure 2 ). Conclusions: Over two decades, the U.S. GON workforce increased substantially, but not equitably, as a widening disparity in rural cancer care was noted over time. Policies and pipeline programs are needed to address this widening disparity in rural gynecologic cancer care.